Odpowiedzi

Najlepsza Odpowiedź!
2010-03-03T19:52:57+01:00
1.
c) -(x+3)+(2x-1)=(1+4x)+(3+x)
-x-3+2x-1=1+4x+3+x
-x+2x-4x-x=3+1+1+3
-4x=8 : (-4)
x=2

2.
a) (3-2x)-(x+4)-(2x+5)=(3x-4)-(5x+7)
3-2x-x-4-2x-5=3x-4-5x-7
-2x-x-2x-3x+5x=-3+4+5-4-7
-3x=-5 : (-3)
x= -5 * (-1/3)
x=5/3
b)(4-x)-(2x+3)+(x-4)=-(2x-3)-(x+7)
4-x-2x-3+x-4=-2x+3-x-7
-x-2x+x+2x+x=3-4+4-7
x=-4
c)(4x-5)+(x-7)-(2x+8)=(-3x+4)-(x-6)
4x-5+x-7-2x-8=-3x+4-x+6
4x+x-2x+3x+x=-5+7+8+4+6
7x=20 : 7
x=7/20
d) -(4-2x)-(2x+4)=(3x-1)+2x-5)-(7-3x)
-4+2x-2x-4=3x-1+2x-5-7+3x
2x-2x-3x-2x-3x=4+4-1-5-7
-8x=5 : (-8)
x=8/5
x= 1 3/5